Effectiveness of Positive Deviance Approach to Promote Exclusive Breastfeeding Practice: A Cluster Randomized Controlled Trial - Siraneh Y; Woldie M; Birhanu Z (Dove Medical Press, 2021)
Yibeltal Siraneh,1 Mirkuzie Woldie,2 Zewdie Birhanu3 1Department of Health Policy and Management, Faculty of Public Health, Jimma University, Jimma, Ethiopia; 2Department of Global Health and Population, Harvard T.H. Chan School of Public Health, Boston, MA, USA; 3Department of Health, Behavior and Society, Faculty of Public Health, Jimma University, Jimma, EthiopiaCorrespondence: Yibeltal Siraneh Email yibeltal_siraneh@yahoo.comBackground: Suboptimal breastfeeding (BF) contributes to a significant number of infant deaths. A positive deviance approach (PDA) was not studied in Ethiopia, whether it improve exclusive breastfeeding (EBF) practice. Therefore, we determined the effectiveness of positive deviant approached intervention in increasing the proportion of EBF practice.Methods: A cluster-randomized controlled trial was employed in Jimma town from February 01 to September 30, 2018. Six randomly selected clusters (kebeles) were randomized into two arms. Then, 260 mothers who met the eligibility criteria were enrolled in either the intervention or control arm depending on where they lived. Women in the intervention group received counseling and social support in addition to the usual service to promote EBF, from women identified and trained as positive deviants in their community, while those in the control groups received the usual community-based services from urban health extension professionals. Data on primary and secondary outcome variables were collected at three points, and statistical difference was estimated using Chi-X2 or Fisher exact test. The net effect of the intervention was calculated. The magnitude of the intervention effect was estimated using the relative risk. For all statistical tests, 95% CI with a P-value of < 0.05 was used.Results: The overall response rate at the endline was 98.8%. Exclusive BF was significantly different between the groups at mid and end points, while no difference at baseline. A higher proportion of mothers in the intervention group reported EBF compared to the control group at mid and end-line. The rate of EBF increased by 18.5% (P=0.01) in the intervention group while 0.2% in the counterparts, with a net effect of +18.2%. The probability of practicing EBF was significantly higher for the intervention group compared to the control group. At baseline, the relative risk of avoiding EBF (RR:1.112) was similar among the two groups. However, at follow-up, mothers in the intervention group were 2 times more likely to practice EBF (RR: 2.294) compared to those in the control group.Conclusion and Recommendation: The PD approach is an effective intervention to promote EBF and also positively affected frequency and duration of BF. Therefore, we recommend the promotion and use of positive deviance approach as a strategy to improve EBF practice in urban settings.Trial Registration Number: Clinical trial PACTR201805003379263, 23 May 2018.Keywords: effectiveness, positive deviance, breastfeeding, exclusive, randomized controlled trial